Efficacy of momordica charantia (bitter melon) supplementation among primary knee osteoarthritis patients : a single-blinded, randomized controlled trial - May, Lim Soo (2018)
Introduction: Osteoarthritis (OA) is a common problem affecting the joints in the elderly, and its conservative treatment includes the usage of analgesia, which frequently leads to undesirable side effects. Traditionally, Momordica charantia (MC) or bitter melon is believed to be effective in relieving pain, including that caused by knee osteoarthritis. Objective: To determine the effects of MC in reducing pain among primary knee osteoarthritis (OA) patients. Methodology: This study involves 75 patients with primary knee osteoarthritis, who were divided into two groups (thirty-eight patients in the MC group and thirty-seven in the placebo group). The patients underwent 3 months daily supplementation of either MC or placebo. Rescue analgesia was allowed as needed, and rescue analgesia intake was recorded. Pain and symptoms during supplementation period were assessed monthly using Knee Injury and Osteoarthritis Outcome Score (KOOS) and EQ-5D-3L (EuroQol- 5 Dimensions- 3 Levels) Health questionnaire. Comparison and analysis between the two groups were done using “repeated measures ANOVA” to determine the changes in KOOS, EQ-5D-3L and analgesic scores after supplementation. Results: After 3 months supplementation period, there were significant improvements in KOOS subscale and EQ-5D-3L score with a reduction in analgesic score. Body weight, BMI and FBS reduced significantly in the MC group. The placebo group had also shown significant improvements in certain KOOS subscale and EQ-5D-3L dimension score, but with increased of analgesic score. Conclusion: Momordica charantia supplementation offers a safe alternative in reducing pain among the primary knee OA patients, while reducing the need for analgesia consumption. These beneficial effects can be seen as early as 3 months of supplementation.